Pengaruh Beban Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan pada PT Global Arrow Jakarta - M. Farhan Simanjuntak; Agtovia Frimayasa (Prisani Cendekia, 2023)
This study aims to investigate the influence of workload and job satisfaction on employee performance at PT Global Arrow Jakarta. A quantitative approach was used in this research, and primary data was collected through the use of questionnaires. The study utilized purposive sampling technique to determine the sample based on specific considerations. The data was analyzed using Multiple Linear Regression with SPSS 24.00. The results of the analysis showed that workload does not significantly influence employee performance, while job satisfaction has a positive and significant impact on employee performance. The ANOVA analysis revealed that both workload and job satisfaction together have a positive and significant influence on employee performance at PT Global Arrow Jakarta.